Challenges concerning the Legal Framework of an Automated Personal Income Tax in Edo State, Nigeria - Aidonojie, Paul Atagamen (Universitas Muhammadiyah Tangerang, 2024)
Concerning the need to curb corrupt income tax practices and to increase internally generated revenue via income tax in Edo State, the Edo State Government 2019 introduced an automated personal income taxing system. However, it must be noted that the income tax procedure in Nigeria is a function of law regulated by the Personal Income Tax Act. Concerning this, there is a legal uncertainty concerning the effectiveness of extant the current legal framework in providing for and regulating an automated personal income tax system in Edo State. It is in this regard, that this study tends to adopt a hybrid method of research in examining to what extent the extant law provides for and regulates income tax in Edo State. The questionnaire was sent to 321 respondents and the data generated therein were analyzed via a descriptive and analytical method. The study found that the Personal Income Tax Act of 2004 does not provide for and regulate an automated income taxing system in Edo State. It was therefore concluded and recommended that for effective compliance with an automated income tax administration in Edo State, there is a need to amend the extant law to provide for an automated income tax procedure.